2014
DOI: 10.3109/13880209.2014.935866
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effects of vanillic acid against streptozotocin-induced neurodegeneration in mice

Abstract: VA exhibited reduction in AChE, TNF-α, and corticosterone with improved antioxidants to contribute neuroprotection and could be an effective therapeutic agent for treating neurodegenerative disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 61 publications
2
45
0
Order By: Relevance
“…Vanillic acid has significant antioxidant activity due to the presence of the carboxyl group (Chou et al 2010). It has also been reported that vanillic acid ameliorates spatial learning and memory retention by preventing oxidative stress (Singh et al 2015). In the present study, DNA damage protection potential of M. nigra extract was also investigated.…”
Section: Discussionmentioning
confidence: 88%
“…Vanillic acid has significant antioxidant activity due to the presence of the carboxyl group (Chou et al 2010). It has also been reported that vanillic acid ameliorates spatial learning and memory retention by preventing oxidative stress (Singh et al 2015). In the present study, DNA damage protection potential of M. nigra extract was also investigated.…”
Section: Discussionmentioning
confidence: 88%
“…In the peripheral system (such as intraperitoneal injection), STZ can directly destroy pancreatic B cells and cause insulin resistance, thus inducing diabetes (3). STZ inducing AD-like pathological changes in rats or mice has also been considered to be a good AD experimental animal model.…”
Section: Discussionmentioning
confidence: 99%
“…It is a commonly used chemical compound for the study of the association between diabetes and AD (3). Peripheral blood vessel or intraperitoneal injection of STZ can selectively destroy pancreatic B cells, causing diabetes, which in turn induces symptoms of AD in mice.…”
Section: Introductionmentioning
confidence: 99%
“…The Y-maze test is used for measuring the spatial working memory in rodents (Singh et al 2015). The percentage of alteration is calculated as the ratio of actual alterations to possible alterations, defined as the total number of arm entries minus two, and multiplied by hundred.…”
Section: Y-mazementioning
confidence: 99%